Peran Media Sosial X Dalam Pemanfaatan Upaya Mitigasi Bencana - Safitri, Annisa Nur; Khalisah, Lulu Nuha; Cecilia, Nayla Assyifa (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
Social media has become a strategic tool in supporting disaster mitigation efforts, including in the rapid and widespread dissemination of information. This study analyzes the role of social media X (formerly Twitter) in supporting disaster mitigation efforts for the eruption of Mount Lewotobi Laki-laki on November 8, 2024. This mountain erupted twice with the eruption column reaching 10 km above the peak, producing thick volcanic ash that affected the surrounding area. The National Disaster Management Agency (BNPB) utilized social media X to provide the latest information, early warnings, and safety guidance to the public. The research method used a descriptive-qualitative approach with content analysis of BNPB's official posts on the X platform. The results showed that social media X was effective in disseminating real-time information, raising public awareness, and coordinating emergency response efforts. In less than an hour after the first eruption, BNPB managed to reach thousands of users with information related to the affected areas, evacuation steps, and health recommendations related to volcanic ash. However, there are challenges such as the potential for the spread of false information that can cause panic in the community. This study confirms that social media X has an important role in disaster risk management. Optimal use of social media, supported by organized information management, can help save lives and minimize the impact of disasters. This study recommends intensive training for BNPB officers in utilizing social media effectively for disaster mitigation.